IMPROVING STUDENTS’ WRITING ANALYTICAL EXPOSITION TEXT ABILITY BY USING GENRE-BASED APPROACH - Imam Muharrom Nurdiana (Journal of English Education Program (JEEP), 2020)
In this research, Genre-Based approach was investigated to know about students’ perceptions and teachers’ experiences in improving students’ writing analytical exposition text. Qualitative research was method chosen to be used with case study because this study focused carried out the detailed description of the study.It used three data collection techniques there are interview, observation, and questionnaire. Observation was analyzed by recording the learning activity by using video during the lesson and transcribed it, questionnaire was analyzed by analyzingand generalizing of the data used percentage computation, and interview was analyzed by presentingand translating the interview into English.In this regard, the participants in this study were the eleventh grade at one of senior high school in West Java. In the finding of this study, referring from the observation and interview data, writer concludes the use of Genre-Based approach can motivate students in learning activities, enhance students how to write properly and effectively. Then,based on the data from questionnaire it shows that most of students argued if the used of Genre Based Approach can improve their motivations and abilities in writing analytical exposition text Finally, a suggestion has been provided for future researchers are recommended to conduct the research with the same topic quantitatively to strengthen the finding of this study. Keywords: Writing, Genre-based approach, Analytical exposition text.